Contribution of dendritic cells to the autoimmune pathology of systemic lupus erythematosus. Issue 4 (12th October 2015) - Mackern‐Oberti, Juan P.; Llanos, Carolina; Riedel, Claudia A.; Bueno, Susan M.; Kalergis, Alexis M.
Summary: Systemic lupus erythematosus (SLE) is a heterogeneous disease in which excessive inflammation, autoantibodies and complement activation lead to multisystem tissue damage. The contribution of the individual genetic composition has been extensively studied, and several susceptibility genes related to immune pathways that participate in SLE pathogenesis have been identified. It has been proposed that SLE takes place when susceptibility factors interact with environmental stimuli leading to a deregulated immune response. Experimental evidence suggests that such events are related to the failure of T‐cell and B‐cell suppression mediated by defects in cell signalling, immune tolerance and apoptotic mechanism promoting autoimmunity. In addition, it has been reported that dendritic cells (DCs) from SLE patients, which are crucial in the modulation of peripheral tolerance to self‐antigens, show an increased ratio of activating/inhibitory receptors on their surfaces. This phenotype and an augmented expression of co‐stimulatory molecules is thought to be critical for disease pathogenesis. Accordingly, tolerogenic DCs can be a potential strategy for developing antigen‐specific therapies to reduce detrimental inflammation without causing systemic immunosuppression. In this review article we discuss the most relevant data relative to the contribution of DCs to the triggering of SLE.